2007
DOI: 10.1159/000112320
|View full text |Cite
|
Sign up to set email alerts
|

Can a Peripheral Artery Be Used to Detect Venous to Arterial Circulation Shunts?

Abstract: Background: Transcranial Doppler is a sensitive test for patent foramen ovale (PFO), but an absent temporal window precludes this in 12–15% of patients. We investigated whether the brachial (BrA), common carotid (CCA) or common femoral (CFA) artery provided reliable alternatives. Methods: Patients underwent simultaneous insonation of a middle cerebral artery (MCA, n = 66) and either (a) the BrA (n = 22), (b) CCA (n = 20) or (c) CFA (n = 24) with a 2-MHz transcranial Doppler probe. Results: The correlation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Moreover, they found in patients in whom RLS could be demonstrated, more bubbles in the ICA than in the MCA. These findings offer indeed the submandibular ICA as an alternative in patients with insufficient temporal bone window, similar to other alternatives such as our transforaminal approach [1], or vertebrobasilar recordings [6], or even more peripheral arteries such as the contralateral brachial or femoral arteries [7]. However, whether the submandibular ICA approach is the most dependable, as Dr Topcuoglu suggests, remains an open question since the different alternatives have still not been directly compared.…”
Section: Dear Sirsmentioning
confidence: 76%
“…Moreover, they found in patients in whom RLS could be demonstrated, more bubbles in the ICA than in the MCA. These findings offer indeed the submandibular ICA as an alternative in patients with insufficient temporal bone window, similar to other alternatives such as our transforaminal approach [1], or vertebrobasilar recordings [6], or even more peripheral arteries such as the contralateral brachial or femoral arteries [7]. However, whether the submandibular ICA approach is the most dependable, as Dr Topcuoglu suggests, remains an open question since the different alternatives have still not been directly compared.…”
Section: Dear Sirsmentioning
confidence: 76%
“…For this purpose, transorbital insonation of the carotid siphon was used in this study [1] . Likewise, cervical insonation of the common carotid artery [4] submandibular insonation of the internal carotid artery [5] , transforaminal insonation of vertebral and basilar arteries [6][7][8] or even insonation of more peripheral arteries, such as the contralateral brachial or femoral arteries [9] , can be performed. However, none of the studies tested the utility of these techniques in patients with insufficient transtemporal bone windows.…”
mentioning
confidence: 99%
“…We read with interest the article by Daly et al [1] about the diagnosis of a right-to-left shunt (RLS) while studying the common femoral artery using a 2-MHz Doppler probe. The authors observed that the common femoral artery emboli count correlated with the count of simultaneous middle cerebral artery (MCA) insonation, concluding that this approach is a reliable alternative to the MCA examination.…”
mentioning
confidence: 99%